2012
DOI: 10.1002/mma.2507
|View full text |Cite
|
Sign up to set email alerts
|

The existence, uniqueness, and regularity for an incompressible Newtonian flow with intrinsic degree of freedom

Abstract: We consider the regularity and uniqueness of solution to the Cauchy problem of a mathematical model for an incompressible, homogeneous, Newtonian fluid, taking into account internal degree of freedom. We first show there exist uniquely a local strong solution. Then we show this solution can be extend to the whole interval [0,T] if the velocity u, or its gradient ∇ u, or the pressure p belongs to some function class, which are similar with that of incompressible Navier–Stokes equations. Our result shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In , it was shown that there uniquely exists a local strong solution ( u , p , ω ) to under some suitable assumptions on initial data. In this paper, we can further show the existence of following small strong solution in Ln(double-struckRn): Theorem Let u0MathClass-rel∈W1MathClass-punc,p(double-struckRn)MathClass-bin∩Lσn(double-struckRn), ω0MathClass-rel∈LnMathClass-bin∕2(double-struckRn) and MathClass-rel∇ω0MathClass-rel∈Lp(double-struckRn) for some p > n .…”
Section: Mathematical Preliminaries and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In , it was shown that there uniquely exists a local strong solution ( u , p , ω ) to under some suitable assumptions on initial data. In this paper, we can further show the existence of following small strong solution in Ln(double-struckRn): Theorem Let u0MathClass-rel∈W1MathClass-punc,p(double-struckRn)MathClass-bin∩Lσn(double-struckRn), ω0MathClass-rel∈LnMathClass-bin∕2(double-struckRn) and MathClass-rel∇ω0MathClass-rel∈Lp(double-struckRn) for some p > n .…”
Section: Mathematical Preliminaries and Resultsmentioning
confidence: 99%
“…But it is worth to point out that, for incompressible Navier–Stokes equations, if one solution is weak, and another one is strong with same initial data, then the two solutions agree with each other (for the details, see the summarization on uniqueness in . Whereas for , there is no similar result, and unique result shown in holds only provided two solutions are strong, because of the strong nonlinear term F ( p ) with respect to pressure.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations